National qualifications framework developments in Europe - (:unkn) unknown (Publications Office of the European Union, 2015)
"The report provides an overview of European national qualifications frameworks (NQFs) and their qualifications, celebrating Cedefop's long-term work in the field and showing that the Centre can make a difference to European vocational education and training and, more importantly, to European citizens. Cedefop has been involved in the conceptualisation and implementation of qualifications frameworks for a long time. In the 1980s it significantly contributed to European cooperation in vocational education and training (VET) by developing a five-level (partly) competence-based structure. This approach directly influenced work at national level, for example influencing the professional qualifications structures of Bulgaria, Estonia, Latvia, Lithuania and Romania. The work on transparency of qualifications starting in the 1990s, within the forum on transparency, directly led to the initial outline of the European qualifications framework (EQF) in 2003-04, a work which became a catalyst for NQF developments during the past decade." (Editor, BIBB-Doku)
Keywords: I 1.2 Anrechnung im Ausland erworbener Leistungen & Abschlüsse; I 2.2 Europa; Nationaler Qualifikationsrahmen; Entwicklung; Europa